Potassium-ion intercalation in anti-NASICON-type iron molybdate Fe2(MoO4)3 - Baskar Senthilkumar; Ramakrishnan Kalai Selvan; Prabeer Barpanda (Electrochemistry Communications, 2020)
Reversible potassium-ion intercalation in anti-NASICON-type iron molybdate Fe2(MoO4)3 is demonstrated for the first time. Submicron-sized Fe2(MoO4)3 particles are synthesized by solution combustion synthesis route using glycine as fuel. The monoclinic anti-NASICON type Fe2(MoO4)3 positive electrode exhibits an initial discharge capacity of ~94 mAh g−1 involving an Fe3+/Fe2+ redox activity centered around 2.6 V (vs. K/K+). Employing ex situ X-ray diffraction, the K+ (de)intercalation is found to involve an underlying solid-solution redox mechanism. This anti-NASICON Fe2(MoO4)3 molybdate is found to be an efficient polyanionic cathode candidate for potassium-ion batteries. Keywords: Potassium-ion batteries, Polyanion, NASICON, Iron molybdate, Capacity